The Effectiveness of Using Collective Numbering on Learning Islamic Jurisprudential Concepts for Jordanian Eighth-Grade Students and their Attitudes towards it - Al -Tamimi, Emad; Al -Tamimi, Eman (Dirasat: Educational Sciences, 2021)
This study aims to investigate the effectiveness of using collective numbering method on the achievement of eighth grade female students in Jordan and their attitudes towards it. Its sample consisted of (34) female students divided into two groups, an experimental group that was taught using collective punctuation method, and a control group that was taught using the usual method. The study used quasi-experimental and descriptive analytical methods. To achieve its objectives, the researchers prepared a test for learning jurisprudential concepts and a scale of attitudes towards the collective numbering method, the validity and stability of which were confirmed. The results showed that there were statistically significant differences at the level (α = 0.05) between the average scores of the experimental group members who studied using collective punctuation method and the average scores of the control group members who studied in the usual way in favor of the experimental group. It also showed positive tendencies towards the use of collective numbering method among female students, with a high degree on most of the questionnaire's paragraphs. The study ended with a set of recommendations, most notably the adoption of collective numbering method in teaching jurisprudence concepts in Islamic education.